Carbon capture, utilization, and storage : separating fact from fiction - Isaacs, Andrew; Coromina, Natàlia Costa I.; Aggarwal, Aditya (London : The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business, 2023)
In 1992, representatives from 179 countries effectively agreed to end the fossil-fuel age at the United Nations Conference on Environment and Development (UNCED) in Rio de Janeiro, Brazil. Yet thirty years later, the Earth Summit's "new blueprint for international action" on environmental issues had not stabilized the climate by stopping the increase of long-lived greenhouse-gas concentrations. In 2022, the United Nations stated, "carbon capture, use and storage (CCUS) can play a significant role in mitigating carbon emissions." Some climate experts considered CCUS necessary for reaching net-zero Greenhouse gas (GHG) emissions. Others thought its technology and infrastructure were so nascent, CCUS was unlikely to make a difference. Had decades-old pledges to stop fossil fuel use been replaced by efforts to capture fossil emissions?
Description based on XML content.
Keywords: elektronické knihy; electronic books; Carbon sequestration -- Government policy -- Case studies; Environmental policy -- International cooperation -- Case studies